2009
DOI: 10.3174/ajnr.a1454
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition Time and Reproducibility of Continuous Arterial Spin-Labeling Perfusion Imaging at 3T

Abstract: SUMMARY:Arterial spin-labeling (ASL) is a relatively new and noninvasive MR imaging technique, used to measure cerebral blood flow (CBF). Scanning time and reproducibility remain important issues in the clinical applicability of ASL. We expected both to benefit from higher field strengths. We describe that when performing ASL at 3T, 20 averages suffice to obtain steady and reproducible CBF values. Scanning time can be as short as 3 minutes.A rterial spin labeling (ASL) is a noninvasive MR imaging technique, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 14 publications
6
29
1
Order By: Relevance
“…Based on the coefficient of variation which was 7.9 % in the global GM ROI, we conclude that the reproducibility of our measurements lies well in the range reported for other pulsed (28)(29)(30) and continuous ASL (31)(32)(33)(34) methods. A recent multi center study at 3T including 28 sites (29) using a PASL method termed QUASAR (35,36) reported values for SD w in GM between 3.01 and 8.12 ml/100 g/min, which suggests that the reproducibility of our measurements is quite high.…”
Section: Discussionmentioning
confidence: 56%
“…Based on the coefficient of variation which was 7.9 % in the global GM ROI, we conclude that the reproducibility of our measurements lies well in the range reported for other pulsed (28)(29)(30) and continuous ASL (31)(32)(33)(34) methods. A recent multi center study at 3T including 28 sites (29) using a PASL method termed QUASAR (35,36) reported values for SD w in GM between 3.01 and 8.12 ml/100 g/min, which suggests that the reproducibility of our measurements is quite high.…”
Section: Discussionmentioning
confidence: 56%
“…CASL, continuous arterial spin labeling; p-CASL, pseudo-continuous arterial spin labeling; s.d., standard deviation; TI PASL, inversion time pulsed arterial spin labeling. on reproducibility of these techniques (Floyd et al, 2003;Gevers et al, 2009a;Hermes et al, 2007;Jahng et al, 2005;Parkes et al, 2004). Looking at mean CBF values and the amount of data dispersion, as indicated by the CVs, we noticed that CASL and single TI PASL data from one site were largely responsible for this discrepancy.…”
Section: Discussionmentioning
confidence: 83%
“…We calculated ICCs for both aCBF and rCBF images; however, it should be noted that previous work showed higher reliability for rCBF measures [21,55,56]. A comparison of aCBF and rCBF was considered to be significant if confidence intervals (95%) for ICCs did not overlap with each other [18]. …”
Section: Methodsmentioning
confidence: 99%
“…Based on previous findings indicating that intra-class correlation coefficients of ASL measures may differ between scans acquired a few hours apart from those acquired several days apart [18,19,21,23,2529,32] and limited information on possible effects of data acquisition using different scans platforms, we aimed to determine the test-retest reliability of ASL measures in these networks across sites/platforms on scans acquired one week apart.…”
Section: Introductionmentioning
confidence: 99%